PT<=> $4(\sqrt{5x^{3}-6x^{2}+2}-1)+4(\sqrt{-10x^{3}+8x^{2}+7x-1}-2)+x-1=0<=>\frac{4(5x^{3}-6x^{2}+1)}{\sqrt{5x^{3}-6x^{2}+2}+1}+\frac{4(-10x^{3}+8x^{2}+7x-5)}{\sqrt{-10x^{3}+8x^{2}+7x-1}+2}+x+1=0<=>(x-1)$(\frac{5x^{2}-x-1}{\sqrt{5x^{3}-6x^{2}+2}+1}+\frac{-10x^{2}-2x+5}{\sqrt{-10x^{3}+8x^{2}+7x-1}+2}+1)=0$<=>x=1$
phần $(\frac{5x^{2}-x-1}{\sqrt{5x^{3}-6x^{2}+2}+1}+\frac{-10x^{2}-2x+5}{\sqrt{-10x^{3}+8x^{2}+7x-1}+2}+1)=0$ giải quyết như thế nào ạ :v
P/s: mình làm ra bài này rồi @@
$VT$ $\leq 2(5x^3-6x^2+3)+(-10x^2+8x^2+7x+3)+x-13=-4(x-1)^2$